2009
DOI: 10.1111/j.1365-2443.2009.01322.x
|View full text |Cite
|
Sign up to set email alerts
|

Replisome progression complex links DNA replication to sister chromatid cohesion in Xenopus egg extracts

Abstract: Cohesin-mediated sister chromatid cohesion is established during the S-phase, and recent studies demonstrate that a cohesin protein ring concatenates sister DNA molecules. However, little is known about how DNA replication is linked to the establishment of sister chromatid cohesion. Here, we used Xenopus egg extracts to show that AND-1 and Tim1-Tipin, homologues of Saccharomyces cerevisiae Ctf4 and Tof1-Csm3, respectively, are associated with the replisome and are required for proper establishment of the cohes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 39 publications
3
57
0
Order By: Relevance
“…30,36 Some models of replication-coupled cohesion suggest that fork uncoupling may take place during interactions between replisomes and cohesin rings, an event that would activate Chk1. 19,20,28,30 Experiments described herein have replicated in genetically stable human fibroblast lines the observation that Tim-Tipin and Claspin contribute to ATR-dependent activation of Chk1 in response to fork uncoupling by DNA damage, namely UVC-induced photoproducts (Fig. 1A and B).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…30,36 Some models of replication-coupled cohesion suggest that fork uncoupling may take place during interactions between replisomes and cohesin rings, an event that would activate Chk1. 19,20,28,30 Experiments described herein have replicated in genetically stable human fibroblast lines the observation that Tim-Tipin and Claspin contribute to ATR-dependent activation of Chk1 in response to fork uncoupling by DNA damage, namely UVC-induced photoproducts (Fig. 1A and B).…”
Section: Discussionmentioning
confidence: 77%
“…30 Reduction of Tim-Tipin and Claspin orthologs/analogs in various systems results in premature separation of sister chromatids in metaphase, a phenotype that could arise from incomplete establishment of cohesion during S phase or precocious removal of cohesins in metaphase. Studies using the Xenopus laevis egg extract system demonstrated that Tim1 specifically was required during replication for full paring of sister chromatids in metaphase, 19 which, taken together with other observations, indicates a role for Timeless orthologs in the establishment of SCC.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations